2010
DOI: 10.1039/b919666h
|View full text |Cite
|
Sign up to set email alerts
|

Scandium triflate-catalyzed one-pot domino approach towards general and efficient syntheses of unsymmetrical 9-substituted xanthene derivatives

Abstract: A general and efficient one-pot cascade/tandem approach to synthesize unsymmetrical 9-aryl/heteroaryl xanthenes has been developed under extremely mild reaction conditions using 10 mol% Sc(OTf)(3) as a catalyst. This strategy has been further extended to synthesize 9-(thioaryl) xanthenes through tandem carbon-sulfur (C-S) and carbon-carbon (C-C) bond formation. Novel C-C and C-S bond cleavage promoted by Sc(OTf)(3) is also discussed during mechanistic investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…31 In addition, they have been used as synthetic precursors for several organic compounds and dyes, [32][33][34] such as uorescents and chiroptical molecular switches (examples include, rosamine, uorone, uorescein, rhodamine etc.). 33,35 The core structure of the xanthene derivatives shows a multitude of physicochemical and pharmacological properties, such as anti-inammatory, 36 antimalarial, 37 analgesic, 38 anticancer, 20 antiviral, 39 antibacterial properties, and so on. 38 Additionally, acridine derivatives, constituting a 1,4-dihydropyridine (DHP) ring skeleton, are very important compounds owing to their pharmacological properties.…”
Section: Introductionmentioning
confidence: 99%
“…31 In addition, they have been used as synthetic precursors for several organic compounds and dyes, [32][33][34] such as uorescents and chiroptical molecular switches (examples include, rosamine, uorone, uorescein, rhodamine etc.). 33,35 The core structure of the xanthene derivatives shows a multitude of physicochemical and pharmacological properties, such as anti-inammatory, 36 antimalarial, 37 analgesic, 38 anticancer, 20 antiviral, 39 antibacterial properties, and so on. 38 Additionally, acridine derivatives, constituting a 1,4-dihydropyridine (DHP) ring skeleton, are very important compounds owing to their pharmacological properties.…”
Section: Introductionmentioning
confidence: 99%
“…To summarize the main syntheses of these studies: in particular, transition metal-catalyzed cascade benzylation-cyclization [9], cyclization of polycyclic aryl triflate esters [10], reaction of β-naphthol and aldehydes [11] or inter-or intramolecular coupling of arynes by aldehydes or phenols [12], and Lewis acid-catalyzed cyclization of salicylaldehydes and cyclohexenones or tetralones [13]. Some other new and prominent synthesis methods of xanthenes are tandem arylation/Friedel-Crafts reaction of o-hydroxy bisbenzylic alcohols with diaryliodonium salts [14], Sc(OTf)3-catalyzed domino reaction [15], and iodine-catalyzed nucleophilic substitution reaction of xanthen-9-ol [16].…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that 2‐aryloxybenzaldehydes and 2‐(arylthio)benzaldehydes undergo domino reaction when treated with 2 equiv. of electron rich (hetero)arenes in the presence of suitable Lewis acid catalyst (Scheme 2b) [16a,b] . Despite these advances, to the best of our knowledge, there is no report for the direct synthesis of unsubstituted 9 H ‐xanthenes and thioxanthenes from the readily available 2‐aryloxybenzaldehydes and 2‐(arylthio)benzaldehydes.…”
Section: Introductionmentioning
confidence: 99%